Boys and girls differ in their rationale behind eating: a systematic review of intrinsic and extrinsic motivations in dietary habits across countries - Deslippe, Alysha L.; Bergeron, Coralie; Cohen, Tamara R. (Frontiers in Nutrition, 2023)
Background Boys' and girls' food habits diverge in adolescence (13–18 years). This contributes to unequal risks of adverse health outcomes based on sex and gender in adulthood (e.g., heart diseases in men vs. disorder eating in women). Though multi-factorial, why these dietary differences occur is unclear. Purpose To identify the reasons why adolescents' motivation behind dietary habits differs among genders. Methods Four databases were searched following PRISMA guidelines. Eligible studies had to use qualitative methodology and report at least one gender unique theme. Reported themes were thematically analyzed, with a sub-analysis by country where the studies were conducted. Quality appraisals were assessed using the Critical Appraisal Skills Programme checklist. Results In the 34 eligible articles (n = 1,694 returned) two overarching themes emerged that dictated dietary habits in adolescents: Self-motivators and Uncontrollable factors. Gender differences arose whereby girls highlighted more external motivators (e.g., eat healthier, change dietary habits around boys and be thin to fit traditional norms) over their dietary habits. In contrast, boys focused on more internal motivators (e.g., gain autonomy, eat for enjoyment and pursue gains in physical performance). This suggests that motivation underlying how boys and girls eat differs. These trends were largely consistent across countries. Conclusion Boys' and girls' food habits are not motivated by the same factors. To create more effective dietary interventions targeting health promotion, unique motivations behind food habits need to be understood and incorporated. Systematic review registration Identifier: CRD42022298077.